PROGRAM PELATIHAN SELF-REGULATED LEARNING UNTUK MENGATASI PROKRASTINASI PADA SISWA SMP DAN SMA VICKERY CHRISTIAN ACADEMY - Kathryn Charissa Ayustyasti Suleiman; Michelle Maria Clarissa Cahanar; Nehemia Adriel Vitardy; Kailey Dyana Hunaidy; Immanuela Dyah Nindhita; Tanaya Sheralea; Penny Handayani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2026)
Vickery Christian Academy (VCA) is a semi-homeschooling-based community where parents who choose to educate their children at home (homeschoolers) become members of the community. Needs analysis conducted through surveys, interviews, and FGD revealed that junior and senior high school students at VCA face challenges in managing their study time independently. This training intervention aimed to enhance students’ self-regulated learning attitude, knowledge, and skills, focusing on time management, goal setting, learning styles awareness, and fostering hope. This training was conducted in person on June 5, 2025, involving 28 students. The implementation methods included interactive lectures, group discussions, and worksheet activities. Evaluation was carried out through pre-test and post-test assessments, the Online Self-Regulated Learning Questionnaire (OSLO), observations, and participant feedback forms. The results showed an average improvement of 13.06% between the pre-test and post-test scores. In addition, the average OSLQ score increased by 6.78%, indicating a positive shift in students’ self-regulated learning behaviors. The training had a positive impact by increasing students’ awareness of time management and their ability to formulate concrete learning goals. In conclusion, self-regulated learning training successfully empowered the VCA community in implementing self-regulated learning in students.